Pedoman kerja sama UIN Sunan Kalijaga Yogyakarta - Universitas_Islam_Negeri_Sunan_Kalijaga_Yogyakarta (Center for Development and Corporation of International Affairs UIN Sunan Kalijaga, 2017)
wd-1/ad,c.1-2